A multiplanar complex resection of a low-grade chondrosarcoma of the distal femur guided by K-wires previously inserted under CT-guide: a case report - Zoccali, Carmine (BioMed Central, 2014)
BACKGROUND: In muscular skeletal oncology aiming to achieve wide surgical margin is one of the main factors influencing patient prognosis. In cases where lesions are either meta or epiphyseal, surgery most often compromises joint integrity and stability because muscles, tendons and ligaments are involved in wide resection. When lesions are well circumscribed they can be completely resected by performing multi-planar osteotomies guided by computer-assisted navigation. We describe a case of low-grade chondrosarcoma of the distal femur where a simple but effective technique was useful to perform complex multiplanar osteotomies. No similar techniques are reported in the literature. CASE PRESENTATION: A 57 year-old Caucasian female was referred to our department for the presence of a distal femur chondrosarcoma. A resection with the presenting technique was scheduled. The first step consists of inserting several K-wires under CT-scan control to delimitate the tumor; the second step consists of tumor removal: in operative theatre, following surgical access, k-wires are used as guide positioning; scalpels are externally placed to k-wires to perform a safe osteotomy. CONCLUSIONS: Computed assisted resections can be considered the most advantageous method to reach the best surgical outcome; unfortunately navigation systems are only available in specialized centres. The present technique allows for a multiplanar complex resection when navigation systems are not available. This technique can be applied in low-grade tumours where a minimal wide margin can be considered sufficient.